GE_GERICHTE P/24616/2023 vom 13. November 2023 - GE Cour de justice (2023)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;VOL(DROIT PÉNAL);APPROPRIATION ILLÉGITIME;ESCROQUERIE;ASTUCE | CPP.310; CP.139; CP.52; CP.137; CP.146